THE ANALYSIS OF SOIL CONSOLIDATION BY CARTIPILLAR UNDERCARRIAGE OF CLAAS LEXION COMBINE HARVESTERS - Іванишин, В. В.; Іліяшик, В. В.; Дуганець, В. І. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
The article focuses on issues of soil consolidation and such after-effect of soil consolidation as poor soil fertility and crop productivity. An analysis of literary sources on the issue was conducted. The characteristics of soil consolidation by combine harvesters are presented. The structural characteristics and operating procedures of DICKEJ penetrometer for soil penetration are given. The study provides the theoretical peculiarities of interaction between soil and caterpillar undercarriage of mobile power unit. The strategies for reducing the negative after-effects of soil consolidation caused by undercarriage of mobile power unit are shown. The comparative analysis of changes in the structure of soil with the help of penetrometer for wheeled and caterpillar undercarriage of LEXION 750 / 600 combine harvesters has been conducted. The analysis has shown that LEXION combine harvesters equipped by caterpillar undercarriage reduced soil and, consequently, soil consolidation